Open Sourcery. - Harrop, Patrick (Journal of Architectural Education, 2007)
The reappropriation of abandoned technology is a long-standing practice with a deep history. This is particularly the case when deprived cultures overlap with privileged. Often associated with the underside of emergent technologies, hacker or maker culture provides us with an alternative approach to engaging technology. This article discusses the potential of implementing hacking as a way of making architecture and poetic program. The Dedale studio at the University of Manitoba investigates the civic and architectural implications of discarded technology in the Point Douglas neighborhood in Winnipeg, Manitoba.